Cadenas productivas y redes de acción colectiva en Medellín y el Valle de Aburrá (2001)
ABSTRACT: The aim of this paper is to present the way in which territorial development and reconfiguration in an urban context, such as the Metropolitan Area of Medellin and Aburrá Valley, is the result of a complex process in which the economic logic of the enterprise actors interacts with the social and political logic of other actors, when they interact in different scenarios and collective action networks. In this scenarios and networks, the intention is to create the discursive conditions -that legitimate and regulate the labour transformations and the social structure that enables new and less expensive productive strategies. In particular, we focus on the issue of economic and social sustainability of territory reconfiguration resulting of that interaction, and whether it produces, or not, enough economic diversification and social implications that allow to confront the contingencies and threats of a changing global environment.